2018
DOI: 10.1159/000487104
|View full text |Cite
|
Sign up to set email alerts
|

Non-Proximal Renal Tubule-Derived Urinary Exosomal miR-200b as a Biomarker of Renal Fibrosis

Abstract: Background: Renal fibrosis is a common outcome of nearly all kinds of chronic kidney disease (CKD) and eventually progresses to end-stage renal disease. The identification of an optimal biomarker of renal fibrosis to replace the invasive renal biopsy will have important clinical implications. Methods: We isolated urinary exosomes from 50 participants and examined the exosomal protein content and particle number in 38 CKD patients with different degrees of renal fibrosis and in 12 normal individuals. We examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…In other studies of CKD, urinary exosomal miR-29c and miR-181a were decreased and correlated with the degree of chronicity or renal fibrosis in CKD patients (Lv et al, 2013;Khurana et al, 2017;Chun-Yan et al, 2018). Urinary exosomal miR-200b was decreased in CKD patients and the degree of decrease was greatest in urinary exosomes derived from cells other than those of proximal renal tubules (Yu et al, 2018). By contrast, urinary exosomal miR-21 was increased in CKD patients and inversely correlated with estimated glomerular filtration rate (eGFR) (Lange et al, 2019).…”
Section: Chronic Kidney Diseasementioning
confidence: 65%
See 1 more Smart Citation
“…In other studies of CKD, urinary exosomal miR-29c and miR-181a were decreased and correlated with the degree of chronicity or renal fibrosis in CKD patients (Lv et al, 2013;Khurana et al, 2017;Chun-Yan et al, 2018). Urinary exosomal miR-200b was decreased in CKD patients and the degree of decrease was greatest in urinary exosomes derived from cells other than those of proximal renal tubules (Yu et al, 2018). By contrast, urinary exosomal miR-21 was increased in CKD patients and inversely correlated with estimated glomerular filtration rate (eGFR) (Lange et al, 2019).…”
Section: Chronic Kidney Diseasementioning
confidence: 65%
“…(Furini et al, 2018) Biomarker Urine (human) Urinary exosomal miR-29c was decreased and correlated with the degree of renal fibrosis. (Chun-Yan et al, 2018) BiomarkerUrine (human) Urinary exosomal miR-200b was decreased in CKD patients and the degree of decrease was greatest in urinary exosomes derived from cells other than those of proximal renal tubules (Yu et al, 2018). Biomarker Urine (human) Urinary exosomal miR-21 was increased in CKD patients and had a negative correlation with eGFR.…”
mentioning
confidence: 99%
“…*P < .05, **P < .01, ***P < .001 biomarkers for the detection of renal diseases. 16 Indeed, exosomal miRNAs have been suggested to participate in pathogenesis of different renal diseases and serve as disease biomarkers, including tubulointerstitial inflammation, 24,25 renal fibrosis, [26][27][28] ischaemic kidney injury, 29,30 IgA nephropathy, 31 acute kidney injury 32,33 and chronic kidney disease. 34 However, the use of circulating exosomal miRNAs for monitoring post-transplant renal graft function has not yet been further explored.…”
Section: Discussionmentioning
confidence: 99%
“…VC is a strong predictor and common complication in patients with ESRD. Yu et al found that the renal tubule-derived urinary exosomal miR-200b could regulate the progression of renal fibrosis, eventually leading to CKD [126]. Lange et al concluded that miR-16 derived from urinary exosomes was the most stable endogenous reference gene in patients with CKD [127].…”
Section: The Role Of Exosomes In Vascular Aging Related Kidney Diseasesmentioning
confidence: 99%